Sustainable growth and environemtnal policies - Santiago J. Rubio; Juana Aznar (Fondazione Eni Enrico Mattei (FEEM), 2000)
A model of ecologically sustainable endogenous growth is presented, in which environmental quality has a positive influence on individual welfare and on the productivity of capital. The effect of different environmental policies on the long-run growth of the economy is studied in the framework of this model. The results establish that an optimal policy which taxes production and subsidises pollution abatement has a favourable effect on environmental quality, and could increase the growth rate if the positive external effects of the environment on the productivity are important. Furthermore, it is shown that this kind of environmental policy is neutral in budgetary terms, i.e. tax receipts are equal to subsidies. Finally, it is demonstrated that a policy based on emission control will only have a positive effect on the growth rate if the initial level of environmental quality is sufficiently low.
Keywords: H23; O41; Q28; 330; sustainable growth; external effects; Pigouvian taxes; emission standards; Neue Wachstumstheorie; Umweltpolitik; Internalisierung externer Effekte; Umweltstandard; Kapitalproduktivität; Theorie